(untitled) (Baghdad Science Journal, 2025)
It is known that the oral administration of ibuprofen caused an irritation of stomach as a side effect due to its carboxylic moiety. Ibuprofen ester was synthesized by linking the carboxylic moiety of ibuprofen and the hydroxylic group of paracetamol to reduce its side effect. Study the kinetic hydrolysis of prepared ester was examined at different values of physiological pH (1.0, 5.8, 6.4 and 7.4) at 37 ± 0.1 of 1 hour period. Measurements of absorbance were carried out by UV-Visible spectrophotometer to follow the stability of ester, it showed Pseudo first order hydrolysis. The pH- apparent rate profiles of ester was exhibited a good stability at pH 1.0 and pH 5.8. Pharmacological activity in vivo of prepared ester was evaluated in relation to analgesic and anti-inflammatory activity using the acetic acid method and the hind paw oedema inhibition, respectively. Acetyl salicylic acid (aspirin) was used as a reference drug for the above tests. The synthesized ester showed higher analgesic and anti-inflammatory action than aspirin.